Ultrasound cardiography examinations detect victims' long-term realized and potential consequences after major disasters: a case-control study - Hidenori Onishi; Osamu Yamamura; Shinsaku Ueda; Muneichi Shibata; Soichi Enomoto; Fumie Maeda; Hiromasa Tsubouchi; Takeshi Hirobe; Sadao Shimizu; Kazuhiko Hanzawa; Tadanori Hamano; Yasunari Nakamoto; et al. (Komiyama Printing Co. Ltd, 2018)
Abstract Background An increase in cardiovascular diseases has been reported following major disasters. Previous work has shown that ultrasonographic findings from ultrasound cardiography examination (UCG) increased until the 44th month after the tsunami caused by the Great East Japan Earthquake. The present study conducted UCG among victims in the tsunami disaster area and investigated the frequency of disaster-related cardiovascular diseases and changes over time until the 55th month after the disaster. Methods The subjects were residents of temporary housing complexes and neighboring housing in Watari-gun, Miyagi Prefecture, Japan. There were 207 subjects in the 18th month, 125 in the 30th month, 121 in the 44th month, and 106 in the 55th month after the disaster. Data were collected through UCG and self-report questionnaire. Results Significant changes were observed among subjects with clinical findings from the UCG, which increased over the study period-from 42.0 to 60.8, 72.7, and 73.6% beginning in the 18th month after the disaster (p < 0.0001). Conclusions It is possible that the UCG can become a useful examination to visualize the potential impact of a major disaster on the cardiac function of victims. Victims with clinical findings continued increasing not only during the acute phase after a disaster but also in the long term. We therefore need to keep this in mind, and note that it is important to establish a support system to control cardiovascular diseases from the early stage of disaster. Trial registration UMIN; ID000029802. R000034050. 2 November 2017.